Long-Term Effect of Early Post-operative Transcutaneous Electrical Stimulation on Voiding Function After Radical Hysterectomy: A Multicenter, Randomized, Controlled Trial - Li, Xiao-wei; Gao, Lei; Wang, Qing; Lv, Qiu-bo; Xia, Zhi-jun; Wen, Hong-wu; Han, Jin-song; Wu, Yu-mei; Wang, Su-mei; Liu, Qing; Li, Huan; Wang, Hai-bo; et al. (Frontiers in Medicine, 2021)
Introduction: Post-radical-hysterectomy (RH) patients suffer from a series of problems resulting from neurovascular injury, such as bladder dysfunction, which reduce their quality of life. We have designed this study to evaluate the efficacy of transcutaneous electrical stimulation (TENS) on patient rehabilitation after RH for early cervical cancer. Materials and methods: A total of 97 patients were enrolled in a randomized-controlled trial (from January 2015 to December 2019) involving 7 medical centers nationwide. Patients were assigned to either the intervention group (n = 46), or the control group (n = 51). TENS was given to patients in the intervention group from the 7th day after surgery for a total of 14–21 days. The control group received no TENS. Primary outcomes were measured for residual urine volume and recovery of urination function. Secondary outcomes were measures for urodynamics (UDS), pelvic floor electromyography function examination (PFEmF), and quality of life (QoL). Results: Residual urine volume and improvement in the rate of urination were found to show no significant differences on the 14th, 21st, and 28th days after surgery. The maximum flow rate (Qmax) in the intervention group was significantly higher than that in the control group on the 28th day, but there were no significant differences in average flow rate, voiding time, time to Qmax, muscle fiber strength, muscle fiber fatigue, and the abnormal rate of A3 reflection on the 28th day and the 3rd mo., as well as in the QoL at 3rd mo., 6th mo., and 12th mo. after surgery. Conclusion: Our study showed no sufficient evidence to prove that TENS under the trialed parameters could improve the subject's voiding function, PFEmF, and QOL after RH. This has provided valuable data for rehabilitation after RH. Clinical Trial Registration:www.ClinicalTrials.gov, identifier: NCT02492542.